463 HYALURONAN DECREASES PULMONARY SURFACTANT INACTIVATION BY PHOSPHOLIPASE A2 IN VITRO. Issue 1 (1st January 2007) - Iwanicki, J. L.; Lu, K. W.; Taeusch, H. W.
Abstract : The treatment of acute respiratory distress syndrome (ARDS) is challenging; patients do not respond well to treatment with various surfactant mixtures. Inflammation leads to increased production of inflammatory mediators such as the enzyme secretory phospholipase A2 (sPLA2), which breaks down both endogenous surfactant and surfactant used for treatment by cleaving phospholipids into lysophospholipids and fatty acids. Not only is surfactant destroyed by this process, but the metabolites also inhibit or inactivate the surface activity of the remaining surfactant. Great interest has developed in finding ways to enable surfactants used clinically to resist inactivation. Hyaluronan (HA) is a unique glycosaminoglycan, and midweight HA (250 kDa) is secreted by alveolar epithelial cells. Previous work by this laboratory has shown that HA added to surfactant reduces inactivation by serum, and Nitzan et al (Rheumatology 2001) have shown that HA decreases hydrolysis of phospholipids in vitro. We therefore hypothesized that HA mixed with surfactant will reduce inactivation caused by sPLA2 and preserve surface activity. Infasurf mixed with HA or Infasurf alone was incubated with sPLA2 and the surface activity was measured using a trough filled with buffer. The surfactant was added to the surface of the buffer, and the equilibrium surface pressure was measured with a metal wire. Prior to incubation with sPLA2, surface pressures were 47.8 ± 0.5 for Infasurf with HA and 47.5 ± 0.4 for Infasurf alone. Infasurf with HA had significantly higher surface pressure after incubation with sPLA2 than Infasurf alone (42.3 ± 1.5 versus 36.3 ± 0.9 respectively, p < .001), indicating better surface activity and decreased inactivation. Additionally, a modified pulsating bubble surfactometer was used to examine surface tension after film compression and expansion. Prior to incubation with sPLA2, minimum surface tension after 5 minutes of cycling was 1.5 ± 1.0 for Infasurf with HA and 4.2 ± 1.6 for Infasurf alone. After incubation with sPLA2, Infasurf with HA had significantly lower minimum surface tension than Infasurf alone (6.9 ± 1.2 versus 19.3 ± 0.8, respectively, p < .001), again indicating decreased inactivation. We conclude that HA reduces inactivation of pulmonary surfactant exposed to sPLA2. Several mechanisms may explain the HA effect: HA could segregate surfactant from the enzyme, thus preventing cleavage of surfactant lipids; HA may improve the function of the remaining surfactant not degraded by sPLA2; HA might prevent the harmful effects of lysophospholipids on the remaining surfactant; or HA may decrease sPLA2 activity by direct interaction with the enzyme.